2020
DOI: 10.3390/ijerph17186444
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Safety Planning: Clinician Training, Comfort, and Safety Plan Utilization

Abstract: Extant literature has demonstrated that suicide safety planning is an efficacious intervention for reducing patient risk for suicide-related behaviors. However, little is known about factors that may impact the effectiveness of the intervention, such as provider training and comfort, use of specific safety plan elements, circumstances under which providers choose to use safety planning, and personal factors which influence a provider’s decision to use safety planning. Participants were (N = 119) safety plan pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…For more information about how to use the template, visit suicidesafetyplan.com. Some clinicians express not knowing how to ask about means and recommending ways to restrict them [93]: the Suicide Prevention Resource Center provides free online training via their Counseling on Access to Lethal Means program [94].…”
Section: What Steps Would You Take Next? What Are Interventions All Suicidal Patients Should Receive?mentioning
confidence: 99%
“…For more information about how to use the template, visit suicidesafetyplan.com. Some clinicians express not knowing how to ask about means and recommending ways to restrict them [93]: the Suicide Prevention Resource Center provides free online training via their Counseling on Access to Lethal Means program [94].…”
Section: What Steps Would You Take Next? What Are Interventions All Suicidal Patients Should Receive?mentioning
confidence: 99%
“…Effective safety plans emphasize agency in treatment (Rogers et al, 2021) and collaboration with practitioners in a manner that clients feel their concerns are heard and understood (Kayman et al, 2015). However, observational studies in hospitals have indicated that safety plans are not always implemented with fidelity and competency (Gamarra et al, 2015;Green et al, 2018), and the results found here may support practitioner calls for further training in safety planning (Moscardini et al, 2020).…”
Section: Discussionmentioning
confidence: 63%
“…The CRP, a core component of BCBT, has been demonstrated to reduce risk of suicide attempt by 76% when compared to TAU (Bryan et al, 2017). The SPI, which is similar in format and content to the CRP, also contains distinct features (e.g., an overt focus on means safety planning; Moscardini et al, 2020). SPI demonstrated improved treatment outcomes over TAU with those randomized to receive a safety plan and follow-up phone calls demonstrating a 45% relative reduction in subsequent suicide attempts at 6-month follow-up assessments (B.…”
Section: The Ccm Of Suicide Prevention Training: Foundation and Appli...mentioning
confidence: 99%